Association between Serum Lipids and Antipsychotic Response in Schizophrenia - Kim, David D. (Curr Neuropharmacol, 2019)
Metabolic abnormalities are serious health problems in individuals with schizophrenia. Paradoxically, studies have noted an association where individuals who gained body weight or who have increased their serum lipids demonstrated a better antipsychotic response. As serum lipids serve as more specific physiological markers than body weight, the objective of this study was to review studies that examined the association between changes in serum lipids and changes in symptoms during antipsychotic treatment in individuals with schizophrenia. A Medline® literature search was performed. Fourteen studies were included and analyzed. Evidence suggests that increases in serum lipids may be associated with decreases in symptoms during antipsychotic treatment. This inverse association may be independent of confounding variables, such as weight gain, and may be most evident during treatment with clozapine. Also, according to recent randomized controlled tri-als, lipid-lowering agents do not appear to worsen symptoms although this needs to be further investigated in clozapine-treated patients. Future studies should investigate the association in question in a larger population and identify underlying mechanisms.